Unbiased plain gradient algorithm for adaptive IIR notch filter with constrained poles and zeros - Punchalard, R.; Lorsawatsiri, A.; Loetwassana, W.; Koseeyaporn, J.; Wardkein, P.; Roeksabutr, A. (My University, 2007)
An unbiased plain gradient (UPG) algorithm for a constrained adaptive IIR notch filter (ANF) is presented in this paper. The proposed algorithm employs the bias removal technique to remove the bias existing in the estimate of the filter parameter, resulting in good estimation. The computer simulation results have shown that the proposed technique is unbiased. ©2007 IEEE.